A expansão dos cursos de pedagogia em Goiânia: um estudo comparativo - OLIVEIRA, Danúsia Arantes Ferreira Batista de (2005)
This work presents an analyze of the expansion of private higher education with profit ends in the context of educational politics in Brazil and also the process of expansion of the pedagogy course in national, regional and local scope. The research objects are the pedagogy course of private sector with profit ends in the city of Goiânia and a comparative study of the pedagogy course from two institutions: Catholic University of Goiás and Faculdades Alves Faria. The study is done through documental research (oral and written sources) in a broader sense, with the perspective of social and historical context, analyzing its macrostructure and respecting its historical particularities and specificities. The research shows the way private higher education with profit ends, that offers pedagogy course in a context of expansion, organizes itself to take part of the competitive market of education in Goiania. The analyses identifies a process of expansion in the higher education sector, especially in the late nineties, with the establishment of new institutions and pedagogy course as well as increase of vacancies. The flux and reflux phenomenon emerges as a response to this expansion boom, which changes the competitive logic of the market. This phenomenon is observed through the number of vacancies, demand, enrolments and the number of graduated students.